2022
DOI: 10.3389/fcvm.2021.750139
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Imaging for the Assessment of Left Atrial Mechanics Across Heart Failure Stages

Abstract: The left atrium (LA) is emerging as a key element in the pathophysiology of several cardiac diseases due to having an active role in contrasting heart failure (HF) progression. Its morphological and functional remodeling occurs progressively according to pressure or volume overload generated by the underlying disease, and its ability of adaptation contributes to avoid pulmonary circulation congestion and to postpone HF symptoms. Moreover, early signs of LA dysfunction can anticipate and predict the clinical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 226 publications
(256 reference statements)
1
6
0
Order By: Relevance
“…These results suggested that VO may result in conduction disorders, which may be associated with the increase of immune responses. These were consistent with recent observations in human beings, showing that conduction disorders were associated with atrial VO, which induces sudden death in patients with AR ( 31 , 32 ).…”
Section: Resultssupporting
confidence: 93%
“…These results suggested that VO may result in conduction disorders, which may be associated with the increase of immune responses. These were consistent with recent observations in human beings, showing that conduction disorders were associated with atrial VO, which induces sudden death in patients with AR ( 31 , 32 ).…”
Section: Resultssupporting
confidence: 93%
“…The use of PALS in place of left atrial volume index (LAVI) may contribute to a more accurate categorization of patients with indeterminate diastolic function (32). Moreover, PALS could provide prognostic significance independent of clinical and echocardiographic assessment, even in patients with HFpEF or normal LA size (32,34). Our meta-analysis further underscored the additional prognostic implication of evaluating LA mechanics in clinical management, overcoming the limitations of LVEF.…”
Section: Discussionmentioning
confidence: 76%
“…24,25 Depletion of compensatory mechanisms translates into overt HF or deteriorated clinical condition. 26 In the advanced stage of HF, LA is enlarged and remodelled to varying degrees with impaired function, which is usually associated with chronic and severe symptoms. 27,28 With the progression of HF, atrial dysfunction may be a late consequence of systemic and pulmonary circulatory changes caused by HF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that abnormal LA function in the early stages of HF is an early indicator of LV diastolic dysfunction 24,25 . Depletion of compensatory mechanisms translates into overt HF or deteriorated clinical condition 26 . In the advanced stage of HF, LA is enlarged and remodelled to varying degrees with impaired function, which is usually associated with chronic and severe symptoms 27,28 .…”
Section: Discussionmentioning
confidence: 99%